The Responsibilities of Engineers. - Smith, Justin; Gardoni, Paolo; Murphy, Colleen (Science & Engineering Ethics, 2014)
Knowledge of the responsibilities of engineers is the foundation for answering ethical questions about the work of engineers. This paper defines the responsibilities of engineers by considering what constitutes the nature of engineering as a particular form of activity. Specifically, this paper focuses on the ethical responsibilities of engineers qua engineers. Such responsibilities refer to the duties acquired in virtue of being a member of a group. We examine the practice of engineering, drawing on the idea of practices developed by philosopher Alasdair MacIntyre, and show how the idea of a practice is important for identifying and justifying the responsibilities of engineers. To demonstrate the contribution that knowledge of the responsibilities of engineers makes to engineering ethics, a case study from structural engineering is discussed. The discussion of the failure of the Sleipner A Platform off the coast of Norway in 1991 demonstrates how the responsibilities of engineers can be derived from knowledge of the nature of engineering and its context.